2016
DOI: 10.1038/srep28743
|View full text |Cite
|
Sign up to set email alerts
|

Two homologous host proteins interact with potato virus X RNAs and CPs and affect viral replication and movement

Abstract: Because viruses encode only a small number of proteins, all steps of virus infection rely on specific interactions between viruses and hosts. We previously screened several Nicotiana benthamiana (Nb) proteins that interact with the stem-loop 1 (SL1) RNA structure located at the 5′ end of the potato virus X (PVX) genome. In this study, we characterized two of these proteins (NbCPIP2a and NbCPIP2b), which are homologous and are induced upon PVX infection. Electrophoretic mobility shift assay confirmed that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…To uncover the mechanism of the enhancing role of P1 SCSMV on PVX pathogenesis, we wanted to explain the mechanism from the perspective of the expression profile of the candidate interacting proteins of PVX-encoded proteins. Twenty-two candidate host proteins—including NbeEF1A (Eukaryotic translation elongation factor 1A) [ 34 ], NbeEF1Bβ1 (Plant translation elongation factor), NbeEF1Bβ2 [ 35 ], NbTIPs [ 36 ], NbFD1 (Ferredoxin 1) [ 37 ], NbREM1–NbREM4 [ 38 ], NbPlastocyanin [ 39 ], NbActins [ 40 ], NbPCIP1-1–NbPCIP1-3 [ 41 ], NbMPB2Cb-1, NbMPB2Cb-2 (TMV-MP30 binding protein 2C, MPB2C) [ 42 ], and NbCPIP1–NbCPIP4 (CP interacting proteins, CPIPs) [ 43 ]—were selected for further analyses of their expression and transcription levels in the presence and absence of P1 SCSMV in N. benthamiana .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To uncover the mechanism of the enhancing role of P1 SCSMV on PVX pathogenesis, we wanted to explain the mechanism from the perspective of the expression profile of the candidate interacting proteins of PVX-encoded proteins. Twenty-two candidate host proteins—including NbeEF1A (Eukaryotic translation elongation factor 1A) [ 34 ], NbeEF1Bβ1 (Plant translation elongation factor), NbeEF1Bβ2 [ 35 ], NbTIPs [ 36 ], NbFD1 (Ferredoxin 1) [ 37 ], NbREM1–NbREM4 [ 38 ], NbPlastocyanin [ 39 ], NbActins [ 40 ], NbPCIP1-1–NbPCIP1-3 [ 41 ], NbMPB2Cb-1, NbMPB2Cb-2 (TMV-MP30 binding protein 2C, MPB2C) [ 42 ], and NbCPIP1–NbCPIP4 (CP interacting proteins, CPIPs) [ 43 ]—were selected for further analyses of their expression and transcription levels in the presence and absence of P1 SCSMV in N. benthamiana .…”
Section: Resultsmentioning
confidence: 99%
“…PVX CP-interacting protein 1 (NbPCIP1 or NbCPIP2) are plant-specific proteins that play an important role as susceptibility factors for viral infections or affect viral replication and movement [ 41 , 43 ]. The qRT-PCR results showed that the expression levels of NbPCIP1-1 , NbCPIP1 , and NbPCIP1-2 were dramatically downregulated, while the expression levels of NbCPIP2 , NbCPIP3 , NbCPIP4 , and NbPCIP1-2 were not altered in chimeric PVX-P1 SCSMV -infected plants compared with PVX-GFP-infected plants ( Figure 7 H,J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CP protein of Rice dwarf virus (RDV) hinders the auxin signaling by targeting the OslAA10 protein of rice thereby resulted in enhanced severity of viral infection [49]. The two homologous protein of N. benthamiana interacts with the CP gene of invading PVX virus and interfere in its encapsidation and movement [50]. Another report revealed that Cucumber mosaic virus -cholrosis inducing strain interacts with choloroplastic ferredoxin I (Fd I) protein, whereas the green mosaic-inducing strain of CMV did not showed this interaction, which suggested that the protein interactions vary with the type of strain of the same virus [48].…”
Section: Discussionmentioning
confidence: 99%
“…Salvianolic acid A (SA) is another natural polyphenolic compound found in Radix Salvia miltiorrhiza , with well reported anti-oxidant and anti-inflammatory properties [ 78 ]. It has been shown that SA can also reverse the HFD-induced obesity [ 79 ]. Indeed, a study conducted with HFD-induced obese mice showed that SA supplementation exerts its anti-obesity effects by activation of WAT browning via the AMPK-SIRT1 pathway [ 80 ].…”
Section: Polyphenol Effect On Obesitymentioning
confidence: 99%